TRIM : Young America's Favorite Physique Publication. (Washington : Trim Enterprise Inc., 1960)
Fonds Suzan Daniel (FSD)
Periodiciteit : tweemaandelijks
Redactie : Box 385, Benjamin Franklin Sation, Washington 4 DC
Engels
Periodiek